Aubergine and Potato Sensitivity with Latex Sensitisation and Oral Allergy Syndrome - A. S. Bansal (Case Reports in Medicine)
Aubergine allergy is rare outside of India and the far east, and very few cases have been reported. We describe a case of aubergine allergy in a 9-year-old girl of Anglo-Indian descent who also had sensitivity to potato, coincidental oral allergy syndrome, and latex sensitisation with mild oral symptoms on consuming kiwi fruit. Specific IgE to aubergine was negative, but skin testing was positive to both raw and cooked aubergine. With early and increased consumption of exotic vegetables in western countries, more cases of aubergine allergy can be expected and negative blood tests do not exclude type 1 sensitivity.